Microalgae Chlorella Vulgaris Harvesting Via Co-Pelletization with Filamentous Fungus (Baghdad Science Journal, 2018)
The objective of this study was to progress another method for coagulation/flocculation of the microalga Chlorella vulgaris via pellet-forming of the fungal species Aspergillus niger which was isolated from municipal wastewater mud and the facultative heterotrophic microalga "C.vulgaris was used. The main factors studies were spore inoculums, organic carbon concentration in medium as well as pH variation which had considerably positive effects on microalgae/fungi co-pelletization formation. The process parameters are an inoculum1×104 spores/ML, 15 g/l sucrose as carbon source and pH ranged from 5 - 7.0 were found optimal for efficient microalgae/fungi co-pelletization formation. For autotrophic growth, when pH of culture broth was adjusted to 5.0 -7.0 with organic carbon addition (15 g/L sucrose), almost complete harvesting efficiency of the microalga was achieved. Furthermore, it was observed that diameter and the concentration of microalgae/fungi pellets were pretentious by the shaker rotation. The new harvesting technology established in this study will decrease the microalga harvesting cost and will be possible to adapt this technique to all microalgal species as an alternative to other old-style harvesting approaches.